Active Variable Geometry Suspension robust control for improved vehicle ride comfort and road holding - Cheng,C; Evangelou,SA; Arana,C; Dini,D (IEEE, 2015)
This paper investigates the design of robust ∞ control for road vehicle Series Active Variable Geometry Suspension (SAVGS). The objective is to improve ride comfort and road holding, while guaranteeing operation inside existing physical constraints. The study utilizes a nonlinear quarter car model that represents accurately the vertical dynamics and geometry of one quarter of a high performance car with a double wishbone suspension. The control objective is to reduce the body vertical acceleration, tire deflection and suspension travel under the impact of road perturbations. Therefore, the selection of the weighting functions for a linear ∞ control, designed for the linearized quarter car, is based on these objectives. The proposed controller is then applied to the nonlinear quarter car model and investigated by nonlinear simulation for a range of road disturbance inputs. The results show that the designed controller when applied on the SAVGS is effective in improving the vehicle ride comfort and road holding.